Upaya Peningkatan Ekonomi Masyarakat dengan Menerapkan Sistem Informasi Publikasi Badan Usaha Milik Desa (BUMDes) Karya Mandiri Di Desa Sagalaherang Kidul Kecamatan Sagalaherang - Suhartono, Agus; Herdian, Caca Arif (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
BUMDes is regulated in Government Regulation of Republic Indonesia No. 11 2021, which explains that BUMDes is a village business formed by the Village Government whose capital ownership and management are carried out by the Village Government and community members, the problems faced by the BUMDes management Karya Mandiri Sagalaherang Kidul Village, Sagalaherang District, namely the difficulty in implementing BUMDes management both in terms of leadership, marketing management, financial management, organizational management and report management. Since it was formed until now, it has not had a web facility to publish products found in its area. The purpose of this service activity is how to build a web-based information system. The method of implementing community service using grounded research and workshop methods. The results that have been achieved are that there has been a web that was built using the CodeIgniter Framework, Unified Modeling Language as an overview of the system design, and using the concept of Model, View, and Control (MVC). The target for the construction of this web will be managed by the management of BUMDes Karya Mandiri and can increase productivity in marketing products produced by the local community.